Implementation of a Functional Semantic Similarity Measure between Gene-Products - Couto, Francisco M. (2009)
Sequence similarity is a common technique to compare gene-products. However, many applications need to compare gene-products based on what they do, not how they are. Most gene-products are being annotated with terms describing their biological function. These terms are defined in biological ontologies. This makes it possible to implement similarity measures between gene-products based on their behavior. We define FuSSiMeG, a functional similarity measure between gene-products that compares the semantic similarity between the terms in their annotations. Software available from http://xldb.fc.ul.pt/rebil/ssm/